Emotional and behavioural difficulties : theory to practice - Cooper, Paul, 1955- (Routledge, 1994)
The authors show that exclusion is not the only option when dealing with children in emotional and behavioural difficulties in mainstream schools. Essential reading for special needs coordinators, teachers and heads.